Distinct class of photoinduced hydrogen-atom-transfer processes: phototautomerizations in molecules with no intramolecular hydrogen bond in the structure. Issue 1 (2nd January 2022) - Lapinski, Leszek; Rostkowska, Hanna; Nowak, Maciej J.
ABSTRACT: Photoinduced hydrogen-atom-transfer processes presented in this review commonly occur in heterocyclic oxo and thione compounds isolated in low-temperature solid-noble-gas or solid-nitrogen environment. Analogous phototransformations were found for simple amides, thioamides and selenoamides. Such photoinduced hydrogen-atom-transfer processes, concerning compounds with no intramolecular hydrogen bond, are fundamentally different from the well-known Excited State Intramolecular Proton Transfer (ESIPT) phenomena. Attempts aimed at finding a mechanism, explaining phototautomerism in compounds where high bariers separate minima of the tautomers in S0 and S1, gave rise to introduction of the hydrogen-atom detachment on the surface of the repulsive πσ* states as a new paradigm of photochemical behaviour of heterocyclic compounds. UV-induced hydrogen-atom-transfer processes allowed photoproduction of new molecular structures never generated using other methods. Transfer of two or three hydrogen atoms was also discovered for some compounds. In most cases, hydrogen atoms were transferred from N-H groups of UV-excited molecules to such heteroatoms as O, S, Se or other N. For some species, hydrogen atoms from other groups, such as OH, SH or NH2, underwent UV-induced transfer to other atom of the molecule. This is the basis of photoreversibility observed for some oxo ↔ hydroxy, thione ↔ thiol or amino ↔ imino phototransformations.